Visual Perception Of The Volumetric Form And Its Interpretation In The Educational Drawing Of The Head At The Initial Stage Of Learning (Eurasian Journal of Learning and Academic Teaching, 2023)
This article is devoted to the peculiarities of the perception of the volumetric form and its interpretation in the educational pattern of the head at the initial stage of training. The volume form is difficult to read, which determines the relevance of the article.